APLIKASI TELEGRAM UNTUK SISTEM MONITORING PADA SMART FARMING : TELEGRAM APPLICATION MONITORING SYSTEM FOR SMART FARMING - Rini Puji Astutik (UPPM Akademi Komunitas Semen Indonesia, 2019)
Industry 4.0, in agriculture, push developing technology which combining automation system and update data exchange via internet technolgoy. The technological developments, in agriculture, in Indonesian have not developed significantly, therefore it is needed a technological development toward industri 4.0. One of the developments in industry 4.0 in agriculture is monitoring system. The goal of this research is to design a monitoring system which conected to internet and using telegram application for accessing data in smart farming. In this research, data, taken, is temperature and moisture soil since both of data are very influencing in plant growth process. Thi design is just a prototype that is used for simulating monitoring process on agriculture land then it is needed temperature and moisture soil sensor for sensing, STM 32 as microcontroller, LCD for displaying monitoring data, bluetooth as connecting to gateway, PC as gateway to connect to internet and android cell phone for installing telegram application. The simulation result show data at IoT device matched to data on telegram application. With telegram application that could access monitoring data from agriculture land will increase agriculture quality result so as implementation of this technology could be one of supporting agriculture development toward industry 4.0